Rare variants in γ‐aminobutyric acid type A receptor genes in rolandic epilepsy and related syndromes. Issue 6 (28th March 2015) - Reinthaler, Eva M.; Dejanovic, Borislav; Lal, Dennis; Semtner, Marcus; Merkler, Yvonne; Reinhold, Annika; Pittrich, Dorothea A.; Hotzy, Christoph; Feucht, Martha; Steinböck, Hannelore; Gruber‐Sedlmayr, Ursula; Ronen, Gabriel M.; et al.
Abstract : Objective: To test whether mutations in γ‐aminobutyric acid type A receptor (GABAA ‐R) subunit genes contribute to the etiology of rolandic epilepsy (RE) or its atypical variants (ARE). Methods: We performed exome sequencing to compare the frequency of variants in 18 GABAA ‐R genes in 204 European patients with RE/ARE versus 728 platform‐matched controls. Identified GABRG2 variants were functionally assessed for protein stability, trafficking, postsynaptic clustering, and receptor function. Results: Of 18 screened GABAA ‐R genes, we detected an enrichment of rare variants in the GABRG2 gene in RE/ARE patients (5 of 204, 2.45%) in comparison to controls (1 of 723, 0.14%; odds ratio = 18.07, 95% confidence interval = 2.01–855.07, p  = 0.0024, p corr  = 0.043). We identified a GABRG2 splice variant (c.549‐3T>G) in 2 unrelated patients as well as 3 nonsynonymous variations in this gene (p.G257R, p.R323Q, p.I389V). Functional assessment showed reduced surface expression of p.G257R and decreased GABA‐evoked currents for p.R323Q. The p.G257R mutation displayed diminished levels of palmitoylation, a post‐translational modification crucial for trafficking of proteins to the cell membrane. Enzymatically raised palmitoylation levels restored the surface expression of the p.G257R variant γ2 subunit. Interpretation: The statistical association and the functional evidence suggest that mutations of the GABRG2 gene may increase the risk of RE/ARE. Restoring the impaired membrane trafficking of some GABRG2 mutations by enhancing palmitoylation might be an interesting therapeutic approach to reverse the pathogenic effect of such mutants. Ann Neurol 2015;77:972–986